Writing and righting literature in the age of human rights - Stonebridge, Lyndsey 1965- (Oxford University Press, 2021)
A bold and accessible argument for the moral and political value of literature in rightless times.The obvious humanity of books would seem to make literature and human rights natural allies. But what is the real connection between literature and human rights? In this short polemical book, Lyndsey Stonebridge shows how the history of human rights owes much to the creative imagining of writers. Yet, she argues, it is not enough to claim that literature is the empathetic wing of the human rights movement. At a time when human rights are so blatantly under attack, the writers we need how arethe political truthtellers, the bold callers out of easy sympathy and comfortable platitudes.
Keywords: Menschenrecht; Literatur; Ethical issues & debates; Human rights